TRUST SEBAGAI VARIABEL MEDIASI DARI E-WOM DAN PERCEIVED VALUE TERHADAP PURCHASE INTENTION HANDPHONE DI SHOPEE - Rachma Putri Puspitasari; Zulfa Irawati (JURNAL LENTERA BISNIS, 2024)
This study aims to analyse E-Wom and Perceived Value on Purchase Intention Handphone at Shopee and Trust as a mediating variable. The method used in this research is quantitative. The population in this study were active students in the Class of 2022, Faculty of Economics and Business, Universitas Muhammadiyah Surakarta (UMS) with the following data. The research sample consisted of 310 respondents, namely active students in the Class of 2022 from the Faculty of Economics and Business, Universitas Muhammadiyah Surakarta (UMS) who used the Shopee application. The purposive sampling method was used in sampling. The type of data analysed is primary data, collected through the use of questionnaires. Data analysis was carried out using the SEM-PLS method through SmartPLS software. The results in this study are E-WOM has a positive and significant impact on Purchase Intention. E-WOM has a positive and significant impact on Trust. Hedonic Value has a positive and significant impact on Purchase Intention. Hedonic Value has a positive and significant impact on Trust. Monetary Value has a positive and significant impact on Purchase Intention. Monetary Value has a positive and significant impact on Trust. Trust has a positive and significant impact on Purchase Intention. Utilitarian Value has a positive and significant impact on Purchase Intention. Utilitarian Value has a positive and significant impact on Trust. Keywords: Trust; E-Wom; Perceived Value; Purchase Intention